2023
DOI: 10.3390/math11092196
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Event-Triggered Consensus Control for Markovian Switched Multi-Agent Systems: A Hybrid Neuroadaptive Method

Abstract: This paper presents a solution to the consensus problem for a particular category of uncertain switched multi-agent systems (MASs). In these systems, the communication topologies between agents and the system dynamics are governed by a time-homogeneous Markovian chain in a stochastic manner. To address this issue, we propose a novel neuroadaptive distributed dynamic event-triggered control (DETC) strategy. By leveraging stochastic Lyapunov theory and matrix inequality methodology, we establish sufficient condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As a result, Zeno behavior can also be ruled out in Case 3. To sum up, if γθ < ln(λ 1 β 1 ) − ln(λ 2 ), the ETM (6) does not exist Zeno behavior.…”
Section: Exclusion Of Zeno Behaviormentioning
confidence: 91%
See 2 more Smart Citations
“…As a result, Zeno behavior can also be ruled out in Case 3. To sum up, if γθ < ln(λ 1 β 1 ) − ln(λ 2 ), the ETM (6) does not exist Zeno behavior.…”
Section: Exclusion Of Zeno Behaviormentioning
confidence: 91%
“…Remark 2. From ETM (6), it has been shown that the designed ETM has two operation modes: triggering at t k−1 + θ or t * k . The first case uses the maximum trigger interval and generates impulses called forced impulses in this paper.…”
Section: Design Of Event-triggered Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the relevant results obtained apply only to the single systems with Markov jump parameters. Particularly, with regard to Markov jump MASs, various control strategies have been proposed to deal with the consensus problem of Markov jump MASs, such as event-triggered control [29,30], output feedback control [31], and robust control [32]. For high-order nonlinear Markov jump MASs, how to achieve target control through the adaptive neural control method needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%